Analisis Persepsi Penggemar K-Pop terhadap Hibriditas Musik Dangdut dan K-Pop pada Acara “Dangdut K-Pop 29THER” - Sajidah, Dinar; Sari, Ratna Permata (Program Studi Ilmu Komunikasi UII, 2025)
The Dangdut K-Pop 29THER event, organized by Indosiar in 2024, combined two distinct genres: dangdut and K-Pop. This study analyzes the perceptions of K-Pop fans in Yogyakarta regarding cultural hybridity in the event, using a descriptive qualitative method through in-depth interviews with five purposively selected respondents. The findings indicate that the respondents generally held positive perceptions, although the acceptance levels varied. Attentional and functional factors were identified as the main aspects influencing their evaluations. Three out of five respondents perceived K-Pop elements as more dominant, particularly in the musical arrangements and the limited use of typical dangdut vocal techniques such as cengkok. The costume and stage aesthetics were also considered to resemble K-Pop idols more closely. This event reflects a process of cultural negotiation within the third space, where K-Pop and dangdut elements adapt to one another, forming a new musical identity without erasing their original cultural essence, thus demonstrating the potential of hybridity in entertainment media.